TEACHING AND LEARNING PROCESS OF SPEAKING - Henny Susanty; Dewi Ritonga; Puan Tursina (Getsempena English Education Journal, 2017)
This study was investigated the process of language teaching and learning of speaking in terms of teaching materials, teaching methods and learning assessments to the students’ at MTsN Blangpidie in the Academic years of 2016/2017. This study was a descriptive research. Two English teachers who taught at MTsN Blangpidie were participated in this study. An Interview was used to collect the data. The data were recorded, transcribed and coded based on the the problems. The finding of the study showed that the teachers at MTsN Blangpidie of South West Aceh used various teaching materials, teaching strategies and also learning assessments.